Influence of calcium on ceramide-1-phosphate monolayers - Oliveira, Joana S. L.; Brezesinski, Gerald; Hill, Alexandra; Gericke, Arne (Beilstein Journal of Nanotechnology, 2016)
Ceramide-1-phosphate (C1P) plays an important role in several biological processes, being identified as a key regulator of many protein functions. For instance, it acts as a mediator of inflammatory responses. The mediation of the inflammation process happens due to the interaction of C1P with the C2 domain of cPLA2α, an effector protein that needs the presence of submicromolar concentrations of calcium ions. The aim of this study was to determine the phase behaviour and structural properties of C1P in the presence and absence of millimolar quantities of calcium in a well-defined pH environment. For that purpose, we used monomolecular films of C1P at the soft air/liquid interface with calcium ions in the subphase. The pH was varied to change the protonation degree of the C1P head group. We used surface pressure versus molecular area isotherms coupled with other monolayer techniques as Brewster angle microscopy (BAM), infrared reflection–absorption spectroscopy (IRRAS) and grazing incidence X-ray diffraction (GIXD). The isotherms indicate that C1P monolayers are in a condensed state in the presence of calcium ions, regardless of the pH. At higher pH without calcium ions, the monolayer is in a liquid-expanded state due to repulsion between the negatively charged phosphate groups of the C1P molecules. When divalent calcium ions are added, they are able to bridge the highly charged phosphate groups, enhancing the regular arrangement of the head groups. Similar solidification of the monolayer structure can be seen in the presence of a 150 times larger concentration of monovalent sodium ions. Therefore, calcium ions have clearly a strong affinity for the phosphomonoester of C1P.
Keywords: calcium; ceramide-1-phosphate; Langmuir monolayers; phase behaviour; structural properties